2017
DOI: 10.1111/cns.12689
|View full text |Cite
|
Sign up to set email alerts
|

Neurotropin® alleviates hippocampal neuron damage through a HIF‐1α/MAPK pathway

Abstract: Neurotropin® exhibited a potent neuroprotective effect on inhibiting Aβ-induced oxidative damage and alleviating Aβ deposition in hippocampus via modulation of HIF-1α/MAPK signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 34 publications
4
32
0
Order By: Relevance
“…Activation of c-Jun N-terminal kinase (JNK) has been reported in APPSwe/PS1dE9 mice to induce long-term synaptic toxicity and cognition impairment (Fang et al, 2017;Liang et al, 2019). Vanadium was demonstrated to decrease phosphorylation of JNK (p-JNK) and thus reduce JNK activation (Wang et al, 2015;Kim and Kim, 2019).…”
Section: Beov Protected Hippocampal and Cortical Synapses Of Ad Modelmentioning
confidence: 99%
“…Activation of c-Jun N-terminal kinase (JNK) has been reported in APPSwe/PS1dE9 mice to induce long-term synaptic toxicity and cognition impairment (Fang et al, 2017;Liang et al, 2019). Vanadium was demonstrated to decrease phosphorylation of JNK (p-JNK) and thus reduce JNK activation (Wang et al, 2015;Kim and Kim, 2019).…”
Section: Beov Protected Hippocampal and Cortical Synapses Of Ad Modelmentioning
confidence: 99%
“…As shown in Fig. 6, exposure to Ab [25][26][27][28][29][30][31][32][33][34][35] ( Though recent researches conjecture that Ab is an immune stress responsed to brain infection. Ab is a savior in the brain tissue rather than a killer.…”
Section: Geniposide Protected Ht22 Cells Against Neurotoxicity Inducementioning
confidence: 99%
“…30 Moreover, recent studies have shown that Ab 25-35 can signicantly promote the nuclear translocation of p65 subunit leading to p65 activation and over-expression of inammatory mediators including TNF-a, IL-1, COX-2 and iNOS. [31][32][33] Hence, the nuclear transport of NF-kB/p65 was observed by immunouorescence test under the uorescent microscope to discriminate the effect of geniposide treatment on nuclear transport of NF-kB/p65 induced by Ab [25][26][27][28][29][30][31][32][33][34][35] . Fig.…”
Section: Geniposide Protected Ht22 Cells Against Neurotoxicity Inducementioning
confidence: 99%
See 2 more Smart Citations